In vitro isoflavonoid production and analysis in natural tetraploid Trifolium pratense (red clover) calluses - Ercetin, Tugba; TOKER, Gulnur; Kartal, MURAT; KARTAL, MURAT; Colgecen, Hatice; Toker, Mehmet C. (My University, 2012)
Isoflavones are polyphenolic phytoestrogens, predominantly found in leguminous plants. Trifolium pratense L., Fabaceae (red clover), is rich in isoflavones that possess estrogenic activity due to their similar molecular structure and effectiveness in preventing health conditions such as menopause, osteoporosis, cardiovascular disease, hypertension and hormone-dependent cancers. In this study, presence and amount of various phytoestrogens in the tetraploid plant and in the calluses derived from the plants were investigated. Calluses were generated from explants obtained from natural tetraploid T. pratense seedlings. The best callus formation was obtained from hypocotyl explants cultured in Phillips Collins and Gamborg B5 media containing different plant growth regulators. Flowers of plants and calluses were analysed for formononetin, biochanin A, genistein and daidzein contents using HPLC. In HPLC analysis, high levels of formononetin (0.249 mu g/mg) were determined in natural tetraploid T. pratense flowers in addition to genistein and biochanin A. In calluses, highest isoflavone content (1.15 mu g/mg formononetin) was observed in modified Gamborg B5 medium. Biochanin A content of calluses and the plant were found to be nearly the same. But formononetin and genistein contents of the calluses in this medium were found to be respectively 4.62 and 21.39 folds higher than the tetraploid plant.